Physiological substantiation and practical implementation of methods of development of strength-building component of endurance training for wrestlers - Tarabrina, N. Yu.; Kraev, Yu. V.; Tikhonov, A.I. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to determine the effects of a complex of high-intensity interval trainings with the use of a "Bulgarian Bag" on the development of special endurance in wrestlers of various qualifications and speed-strength fitness level.